THE CONTENT OF THE PRIMARY SCHOOL TEACHER'S USE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE CLASSROOM - Saliyeva Perdexan Alimbetovna (American Journals Publishing, 2025)
In accordance with modern requirements, it provides for the development of professional knowledge, skills and qualifications of pedagogical staff of secondary schools, systematic improvement of their professional competence. Aimed on the formation of knowledge, skills, qualifications and competencies in order to improve the quality of education.
Keywords: Continuous Professional Development System, Pedagogical Ethics and Communication Culture, Professional Development, Professional Activity